Construction electrical contracting - Traister, John E. (New York : John Wiley & Son, Inc., 1978)
This book is designed to orient reader whether he is thinking of entering the business or is already active in the industry to the responsibilities and risks involved in the business of electrical contracting, the technical performance required, and all other aspects of the business. A knowledge of all phases covered in this book will help to provide a more profitable business operation and to prevent failure.
Introduction to electrical contracting -- 2. Preliminary construction techniques -- 3. Preliminary -- 4. Job management techniques -- 5. Basic installation practices -- 6. Branch circuit installation techniques -- 7. Service and feeder wiring -- 8. Special systems -- 9. Lighting fixture installations -- 10. Personnel management -- 11. Competing the project -- 12. Operating costs and profit -- 13. Cost accounting -- 14. Electrical drawings -- 15. Electrical specifications -- 16. Fundamental estimating techniques -- 17. Wiring system take-off -- 18. Applying labor units -- 19. Summarizing the estimate -- Glossary -- Index.
Keywords: ELECTRICAL CONTRACTING